Wind Energy Potential at Badin and Pasni Costal Line of Pakistan - Kaloi, Ghulam Sarwar; Wang, Jie; Baloch, Mazhar H; Tahir, Sohaib (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Unfortunately, Pakistan is facing an acute energy crisis since the past decade due to the increasing population growth and is heavily dependent on imports of fossil fuels. The shortage of the electricity is 14-18 hours in rural areas and 8-10 hours in urban areas. This situation has been significantly affecting the residential, industrial and commercial sectors in the country. At this time, it is immense challenges for the government to keep the power supply provision continue in the future for the country. In this situation, it has been the increased research to explore renewable energy resources in the country to fulfill the deficit scenario in the state. The renewable energy sector has not penetrated in the energy mix, currently in the upcoming markets. This paper highlights the steps taken by the country in the past and is taking steps at the present time to get rid of from the existing energy crisis when most urban areas are suffering from power outages for 12 hours on regular basis. Until 2009, no single grid interconnected wind established, but now the circumstances are changing significantly and wind farms are contributing to the national grid is the reality now. The initiation of the three wind farms interconnection network and many others in the pipeline are going to be operational soon. The federal policy on wind energy system has recently changed. Surprisingly, the continuing schemes of the wind farm are getting slow. This paper reviews developments in the wind energy sector in the country and lists some suggestions that can contribute to improving the penetration of wind energy in the national energy sector.Article History: Received Dec 16th 2016; Received in revised form May 15th 2017; Accepted June 18th 2017; Available onlineHow to Cite This Article: Kaloi,G.S., Wang, J., Baloch, M.H and Tahir, S. (2017) Wind Energy Potential at Badin and Pasni Costal Line Pakistan. Int. Journal of Renewable Energy Development, 6(2), 103-110.https://doi.org/10.14710/ijred.6.2.103-110